Mental Revolution Through Missionary Endeavor Counselling on the Accusative of HIV and AIDS (PLWHA) in Pemalang Regency - Purnama Rozak (Jurnal Hikmatuna, 2018)
This society submission is to revolutionize the society’s negative point of view toward PLWHA and PLWHA’s mental, to describe PLWHA’s condition in Pemalang regency and the process of missionary endeavor counselling to the HIVAIDS sufferer (PLWHA) in Pemalang Regency that was conducted by lecturer of Sekolah Tinggi Agama Islam Negeri (STAIN) Pekalongan. The implementation of this program included early study, discussion, socialization, workshop and handing cloth aid to PLWHA. This submission was held in Pemalang Regency used PAR method through observation, discussion, socialization and workshop and training. The HIV AIDS sufferer in Pemalang was early reported in 1993 for one case that discovered in West Java and died as AIDS case in 14 October 1995, until December 2014 Pemalang Health Department reported more than 100 cases that consisted of 55 HIV diseases, 45 AIDS diseases and 35 died. HIV AIDS caused concerned economic-social impact. Based on the early study and discussion, the problems are the less knowledge of society about the HIV AIDS spreading, society still isolated the HIV AIDS sufferer from social intercourse, the PLWHAs are mostly less of confidence, the less of PLWHA’s ability, society is less of dare to get HIV AIDS test. According to the problems above, the next process is socialization, workshop and training, handing cooking tools aid that used as an activity to give a solution in solving those problems. The scope of the activity zone included HIV AIDS sufferer (PLWHA) 40 people. the process of this submission program started from early study, socialization, workshop, and handing help, evaluation and guiding. The socialization program result is missionary endeavor knowledge, HIV AIDS, consciousness to respect and give empathy to HIV AIDS sufferer, and society would be stayed away from HIV AIDS disease. Whereas workshop and handing held is for to increase the capacity, confidence and ability of PLWHA. The team also set aside person as a consulted and associated place with counselor and LSM to guide PLWHA. The evaluation result is monitoring program and evaluation program with reporting activity (reporting activity program).